2021
DOI: 10.3889/oamjms.2021.5692
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Quality of Life among Beta-Thalassemia Major Patients Attending the Hematology Outpatient Clinics at Cairo University Hospital

Abstract: AIM: This paper aimed at assessing the quality of life (QoL) among beta (β)-thalassemia major patients using the short-form-36questionnaire (SF-36) and determining the factors associated with it. METHODS: A cross-sectional study was conducted among β-thalassemia major patients who were attending the hematology outpatient clinic at Cairo University Hospital using the consecutive sampling technique. Data were collected between October 2016 and March 2017. The QoL was assessed for patients aged ≥17 years. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
2
3
0
Order By: Relevance
“…They concluded that children with thalassemia had a poor QOL on pretest, and conditions like high hemoglobin level and low iron overload were associated with improved QOL scores. In addition, this result agreed with Hamdy et al, (2021) in their study about "Assessment of Quality of Life among Beta-Thalassemia Major Patients Attending the Hematology Outpatient Clinics at Cairo University Hospital". They reported that QoL in thalassemia major patients is compromised.…”
Section: Effect Of Self -Determination Theory Based Intervention On Q...supporting
confidence: 87%
“…They concluded that children with thalassemia had a poor QOL on pretest, and conditions like high hemoglobin level and low iron overload were associated with improved QOL scores. In addition, this result agreed with Hamdy et al, (2021) in their study about "Assessment of Quality of Life among Beta-Thalassemia Major Patients Attending the Hematology Outpatient Clinics at Cairo University Hospital". They reported that QoL in thalassemia major patients is compromised.…”
Section: Effect Of Self -Determination Theory Based Intervention On Q...supporting
confidence: 87%
“…The age during the first transfusion was significantly correlated with physical function; the older the children received the first transfusion, the better the physical function. Hamdy et al (2021) found similar results, in which the age when received the first transfusion was significantly correlated with children's quality of life score. Sazlina et al (2015) proved that children who received their first transfusion before four years old had a lower quality of life total score than those who received their first transfusion after four years old.…”
Section: Age During the First Transfusionsupporting
confidence: 62%
“…Females tend to report lower health-related QoL scores than males. 30 , 34 , 38 , 42 In addition, females may be more willing to discuss symptoms and reporting of health-related QoL than males. 26 Females without social support who are exposed to life events are more vulnerable than males.…”
Section: Discussionmentioning
confidence: 99%
“…Twelve out of sixteen studies investigated gender differences concerning QoL. [27][28][29][30][31]34,[36][37][38][39][40]42 Four studies found that women had reduced QoL in terms of lower satisfaction with physical health, psychological health, and social relationships, 34 lower vitality domain, 38 bodily pain, and physical health summaries, 42 and faced more problems on daily activity than males. 30 Contrary to those results, two studies found that females had better QoL 27 and significantly higher scores in the overall perception of the health domain.…”
Section: Quality Of Lifementioning
confidence: 99%